Cervical region trigger point Injection with dry needling versus wet needling by lidocaine in geriatric population: a comparative study - Dalia A. Ibrahim; Hesham A. Abdelrahem (Ain Shams Journal of Anesthesiology, 2019)
Abstract Background Myofascial pain syndrome is a common musculoskeletal disorder which is characterized by presence of trigger points. Its prevalence is up to 60% in geriatric population, and local treatment is important due to the limitation in prescribing systemic pain killer for that population with multiple comorbidities, and the polypharmacy they have. Objectives This clinical trial aimed to compare between lidocaine injection 0.5% (wet needling) and dry needling “DN” (both are local techniques) in treatment of chronic neck pain in geriatrics. Materials and methods Forty elderly participants (above age of 60) who met the inclusion criteria and had a typical trigger point (MTrP) were allocated randomly in two groups, wet needling by lidocaine injection 0.5% versus dry needling. Measures which were taken pre- and post-treatment in each group and post-treatment for both groups were compared together. These measures were pain score and visual analog scale (VAS) for pain, patient satisfaction, and patient discomfort. Results Comparison of the post-treatment results in both groups showed that PS was significantly improved in both groups while VAS was significantly improved in the lidocaine group but improvement of VAS in the dry needling group (DNG) was non-significant. Comparison between the two groups in the post-treatment visit revealed non-significant difference between the two groups as regards PS but VAS in group I (lidocaine group) is significantly lower than that in group II (DNG), also significant higher patient satisfaction and significant lower patient discomfort in group I than in group II, and burning sensation was significantly higher in group II than in group I. Conclusion Dry needling still has some positive results yet. Wet needling by lidocaine was associated with rapid patient satisfaction and less discomfort and was proved to be practical for treatment of myofascial trigger point (MTrP). So, wet needling by lidocaine for MTrPs in geriatric population is a good choice.